Thermal performance enhancement of a circular tube fitted with inclined perforated disk inserts - Mehta, Rajesh; Gupta, Anirudh; Kumar, Nitin; Eiamsa-ard, Smith; Thianpong, Chinaruk; Chuwattanakul, Varesa; Chamoli, Sunil (My University, 2026)
Heat exchangers are crucial devices in industries, and enhancing their thermal performance while controlling pressure losses remains a significant challenge. This paper examines the idea that inclined perforated disk (IPD) inserts can be effectively used to improve heat transfer in circular tubes with constant heat flux conditions at acceptable levels of hydraulic penalties. Turbulent airflow with Reynolds numbers (Re) ranging from 5000 to 21,000 was examined in experiments, and three perforation indices (PI = 0.21, 0.24, and 0.27) were tested to determine the effects of hole density on thermal and hydraulic performance. Evidence showed that the Nusselt number (Nu) had been improved by over 86 % compared to plain tubes, with the thermal enhancement factor (TEF) reaching as high as 1.53 at PI = 0.27 and Re = 5000. Particle swarm optimization (PSO) and neural network modelling multi-objective optimization were used to test the results of the experiment and determine the best operating conditions at PI = 0.21. The paper has demonstrated that inclined perforated disk inserts can form a viable passive method for enhancing the efficiency of heat exchangers, as the swirl and jet flow patterns created by the perforations effectively break the thermal boundary layer, thereby increasing the rate of convective heat transfer.
Keywords: Heat transfer enhancement; Inclined perforated disk inserts; Particle swarm optimization, thermal-hydraulic performance; Passive heat exchanger augmentation